FROM RECRUITMENT TO VALUE CREATION: A SUSTAINABLE VALUE-BASED DIFFERENTIATION MODEL FOR PRIVATE UNIVERSITY - Mirza Khairusy; Didit Haryadi; Alfian Putra; Yuda Prameswari; Reni Febriani (Faculty of Economic and Business, University of Pasundan, 2026)
This study examines how Sustainable Value-Based Differentiation (SVBD) enhances Sustainable Marketing Outcomes (SMO) in private universities operating within spatially concentrated higher education markets. Specifically, it investigates the mediating roles of Perceived University Distinctiveness (PUD) and Student Trust (ST). A quantitative explanatory approach was employed using data collected from 140 students across five private universities in Kota Serang, Indonesia. The findings reveal that SVBD significantly strengthens institutional distinctiveness and student trust, which subsequently improve students’ loyalty intention, positive word-of-mouth, and engagement. The study demonstrates that sustainable competitive advantage is achieved through a multi-stage value creation process in which cognitive (PUD) and relational (ST) mechanisms translate value-based differentiation into sustainable marketing outcomes, extending conventional recruitment- and attribute-based approaches in higher education marketing.